Executive Bonds: Definition and Legal Conditions according to the Jordanian Shari’a Execution Law No. (10) of 2013 - Al-Nabulsi , Moawiah Hassan A.; Al-Braishi , Isma’el Mohammad Hasan (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: This study aims to determine the legal form of executive bonds according to the valid Shari’a execution law. It achieves this purpose by clarifying the concept of executive bonds and their legal conditions that are necessary for the fulfillment of compulsory execution in the Shari’a execution 1courts. Methods: The study uses the inductive approach in tracing legal materials, law-related jurisprudential terms, Islamic and legal jurisprudence books, and jurisprudence. Results: The study concludes that executive bonds are specific official documents that cannot be challenged except by forgery. It also reveals that the legal form of executive bonds has two aspects, namely form (which refers to the subject of the bond that is stipulated in the law in a way that facilitates its accurate implementation) and content (which indicates that the right demanded by the bond is achievable and specified by quantity or description). Finally, it shows that the right should be acquired on the spot rather than pending a deadline. Conclusions: The legal form of executive bonds must be considered to guarantee an accurate execution process and prompt justice. Hence, the study recommends the issuance of a procedural guide on this subject by the Department of the Chief Justice. The guide should deal with the concept of executive bonds and their legal conditions in a detailed, practical, and simplified manner. In addition, it should be observed by the judges and employees of the execution courts as well as by the litigants.